Adaptive management intentions with a reality of evaluation: Getting s cience back into policy - Hasselman, Lyndal (Environmental Science & Policy, 2017)
In Australia’s Murray-Darling Basin water reform has been contentious as government attempts to reconcile historical over allocation of wate r to irrigation with the use of water for environmental outcomes. Howe ver, in many aspects, scientific knowledge of the environment is eithe r imperfect, incomplete or environmental responses are unpredictable, with this uncertainty preventing definitive policy and closure of poli tical arguments. In response to uncertainty and knowledge gaps, adapti ve management has been written into the legislation, along with provis ions for periodic evaluation. This research ascertains how adaptive ma nagement is understood by policy makers, with this indicative of futur e implementation of adaptive management. The way in which adaptive man agement is constructed by policy makers is determined through legislat ion, public speeches, government reports and semi-structured interview s. The findings demonstrate that adaptive management has been subsumed by evaluation. The loss of adaptive management as a distinct concept is seen as a loss of science and discovery from the policy process, wi th the dominance of evaluation discussed as limiting innovation and re inforcing a ‘muddling through’ of policy.
Keywords: Accountability; Adaptive Management; Evaluation; Science; Uncertainty